2017
DOI: 10.1159/000480419
|View full text |Cite
|
Sign up to set email alerts
|

The Long Non-Coding RNA XIST Interacted with MiR-124 to Modulate Bladder Cancer Growth, Invasion and Migration by Targeting Androgen Receptor (AR)

Abstract: Backgrounds/Aims: Long non-coding RNA (lncRNA) X-inactive specific transcript (XIST) is involved in the progression of several tumors. The interaction between lncRNA and miRNA or miRNA’s target genes is reported to play crucial roles in malignancy. In addition, Androgen receptor (AR) is considered to be involved in bladder cancer progression. In this study, we investigated the role of XIST in human bladder cancer and its interaction with miR-124 and AR. Methods: XIST and AR expression was detected in bladder t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
80
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(85 citation statements)
references
References 51 publications
5
80
0
Order By: Relevance
“…Recent studies suggest that lncRNAs can suppress the expressions and biological functions of miRNAs by functioning as a molecular sponge or a competing endogenous RNA (ceRNA), hence leading to derepression of its target mRNA [17]. Interestingly, XIST was reported to directly interact with miR-124 to modulate bladder cancer progression [18]. Therefore, this study was designed to investigate whether XIST could interact with miR-124 to participate in the regulation of DOX resistance in CRC.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggest that lncRNAs can suppress the expressions and biological functions of miRNAs by functioning as a molecular sponge or a competing endogenous RNA (ceRNA), hence leading to derepression of its target mRNA [17]. Interestingly, XIST was reported to directly interact with miR-124 to modulate bladder cancer progression [18]. Therefore, this study was designed to investigate whether XIST could interact with miR-124 to participate in the regulation of DOX resistance in CRC.…”
Section: Introductionmentioning
confidence: 99%
“…Consistently, in this study, we found that HHLA2 is upregulated in BUC tissues compared with normal tissues, and high HHLA2 expression predicts poor survival in BUC patients. BCa is manifested with highly recurrent multiple tumors [22,23]. Clinical tumor staging, pathological grade, and lymph node metastasis have been proven to be vital predictors of clinical prognosis [24].…”
Section: Discussionmentioning
confidence: 99%
“…For example, microRNAs may regulate the proliferation, migration, invasion [4, 5] and the chemo-sensitivity [6] of bladder cancer. Long Non-coding RNAs also showed huge functions in bladder cancer,including tumorigenesis, growth [7], apoptosis [8], metastasis [9] and so on. Recently, circRNAs have been found own great influence in cancer.…”
Section: Introductionmentioning
confidence: 99%